Democracy and federalism in the European Union and the United States : exploring post-national governance - Fabbrini, Sergio (London ; New York : Routledge, 2005)
The European Union - a supranational system with its own institutional characteristics and autonomy - has a structure and functional logic which are more similar to those of the US than those of European nation states. Yet, by and large, the EU and the US tend to be analyzed more as potential geopolitical and economic rivals or allies than compared as institutional peers. By bringing together some of the most influential political scientists and historians to compare the European and American experiences of federalism, Democracy and Federalism in the European Union and the United.
Is the Eu exceptional? The EU and the US in comparative perspective / Sergio Fabbrini -- European federalism: past resilience, present problems / Mark Gilbert -- The constitutionalization of the EU: steps toward a supranational polity / Alec Stone Sweet -- The emergence of the EU supranational polity and its implications for democracy / James A. Caporaso -- Nation and federalism in the American historical experience: a model for Europe? / Edoardo Tortarolo -- Territory, electorates and markets in the US: the construction of democratic federalism and its implications for the EU / Alberta M. Sbragia -- citizens in American federalism: locating accountability in a dispersed system / Bruce E. Cain -- Building a market without a state: the EU in an American perspective / Sergio Fabbrini -- European polity-building: searching for legitimacy between economic and social Europe / Vincent Della Sala -- Is social capitalism exportable? Considerations from the EU enlargement / Donald Sassoon -- Post-national democracy as post-national democratization / Alberta M. Sbragia -- The EU and the challenge of a post-national constitution / Yves Mény -- Is international democracy possible? A critical view / Robert A. Dahl.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: European Union; European Union; Federal government -- European Union countries; Federal government -- United States -- History; Democracy -- European Union countries; Democracy -- United States; POLITICAL SCIENCE -- Civics & Citizenship; Democracy; Federal government; European Union countries; United States; History